Peramalan Curah Hujan dengan Pengelompokan Bulan Menggunakan Metode Double Exponential Smoothing dari Brown - Yuda Novianto; Yessica Nataliani (Jurusan Informatika Universitas Tanjungpura, 2022)
It is important to know the future rainfall, the way is to predict rainfall. By knowing future rainfall, development strategies such as irrigation, dams, urban drainage, harbour docks, agriculture, and even disaster mitigation strategies will be right on target. The purpose of this study is to predict the rainfall for Boyolali Regency and Surakarta City, Central Java in 2020-2021 with Brown's double exponential smoothing method. The type of data used is secondary data, which is obtained from the Meteorology, Climatology and Geophysics Agency of Semarang Climatology Station. The smoothing value, alpha, used in each month was varies, because the rainfall data is grouped first based on the same month, before it was forecasted. The results showed that the highest rainfall in 2020 was 490.73 mm (April) and the lowest was 3.25 mm (August). While for 2021, the highest rainfall was 521.37 (April) and the lowest was 3.25 mm (August), with an MSE of 14731.56, RMSE of 121.37, MAD of 97.42, and SSE of 176778.69.